Optimization of Production Processes through Lean Manufacturing Techniques in the Automotive Industry - Dewadi, Fathan; Suhara, Ade; Aulia Nanda, Rizki; Karyadi, Karyadi; Amir, Amir (YCMM, 2024)
The objectives of this study are to identify and analyze the most effective Lean Manufacturing techniques in improving the efficiency of the production process in the automotive industry and identify the types of waste that occur in the automotive production process and develop strategies to reduce or eliminate them through the application of Lean ManufacturingMethod in this study is to identify the main themes in the literature regarding Lean Manufacturing techniques, implementation challenges, and impacts on production efficiency and quality, combine the analysis results to provide a comprehensive picture of Lean Manufacturing implementation, including best practices and recommendations, assess the quality and relevance of the literature, and identify gaps in existing research. Lean implementation often faces challenges such as change resistance, resource limitations, and the need for intensive training. Literature studies note that successful Lean implementation depends on managerial support and organization-wide commitment. Lean techniques are proven to improve production efficiency by reducing cycle time, decreasing lead time, and improving material flow. 5S techniques improve organization and cleanliness in the workplace. Identification of the types of waste in the automotive production process can significantly reduce or eliminate such waste. Well-implemented Lean techniques can reduce costs and improve product quality simultaneously, providing mutually supportive benefits and increasing customer satisfaction and company profitability.